TITLE: ENHANCING PHLEBOTOMY SKILLS: EVALUATING THE EFFECTIVENESS OF ADVANCED TRAINING FOR MEDICAL NURSING STAFF - SA, Amina; Yassir, Shaheena (International Journal of Pharma and Bio Sciences, 2026)
Introduction: About 60% of pre-analytical errors in clinical laboratories are caused by in vitro hemolysis. A blood sample’s hemolysis could result in inaccurate estimations of the true concentrations and levels of various analytes in the blood. Apart from this, it causes unnecessary pain and discomfort of the patient and delay in diagnosis. Therefore, the purpose of the current study was to assess the effectiveness of medical nursing training using the sample rejection rate due to of hemolysis. Materials and Methods: The research study was a pre and post interventional time bound study on the data pertaining to hemolysed samples received in the Biochemistry Department, Yenepoya Medical College Hospital Central Laboratory, during the time period from October 2022 to February 2022. Samples rejected due to hemolysis were analysed and training were given to the medical nursing staff by certified phlebotomists. Data were collected two months before and two months after the training, from the sample rejection book maintained in the Laboratory. The McNemar test was used to assess whether the training is helpful to decrease the proportion of hemolyzed samples. Results: The rate of hemolysed samples decreased significantly in the month of training with the p value of < 0.0001 on comparing the rate of hemolysis before training. The rate of hemolyzed samples before training and during the intervention month differed significantly (2.2% vs. 1.35%). Conclusion: The training demonstrated a significant short-term effect in reducing the rate of hemolysed samples; however, the long-term impact remains inconclusive. Since accurate laboratory test results are crucial for clinical decision-making, implementing frequent training sessions and ongoing medical education programs for medical staff can further lower the rate of hemolyzed samples, improve the quality of laboratory results, and improve clinical outcomes.